Rethinking methane from animal agriculture - Shule Liu; Joe Proudman; Frank M. Mitloehner (CABI Agriculture and Bioscience)
Abstract Background As the global community actively works to keep temperatures from rising beyond 1.5 °C, predicting greenhouse gases (GHGs) by how they warm the planet—and not their carbon dioxide (CO2) equivalence—provides information critical to developing short- and long-term climate solutions. Livestock, and in particular cattle, have been broadly branded as major emitters of methane (CH4) and significant drivers of climate change. Livestock production has been growing to meet the global food demand, however, increasing demand for production does not necessarily result in the proportional increase of CH4 production. The present paper intends to evaluate the actual effects of the CH4 emission from U.S. dairy and beef production on temperature and initiate a rethinking of CH4 associated with animal agriculture to clarify long-standing misunderstandings and uncover the potential role of animal agriculture in fighting climate change. Methods Two climate metrics, the standard 100-year Global Warming Potential (GWP100) and the recently proposed Global Warming Potential Star (GWP*), were applied to the CH4 emission from the U.S. cattle industry to assess and compare its climate contribution. Results Using GWP*, the projected climate impacts show that CH4 emissions from the U.S. cattle industry have not contributed additional warming since 1986. Calculations show that the California dairy industry will approach climate neutrality in the next ten years if CH4 emissions can be reduced by 1% per year, with the possibility to induce cooling if there are further reductions of emissions. Conclusions GWP* should be used in combination with GWP to provide feasible strategies on fighting climate change induced by short-lived climate pollutants (SLCPs). By continuously improving production efficiency and management practices, animal agriculture can be a short-term solution to fight climate warming that the global community can leverage while developing long-term solutions for fossil fuel carbon emissions.